Applications of nanorefrigerant and nanolubricants in refrigeration, air-conditioning and heat pump systems: A review - Alawi, Omer A. (Elsevier Ltd., 2015)
Nanorefrigerants are a special type of nanofluids which are mixtures of nanoparticles and refrigerants and have a broad range of applications in diverse fields for instance refrigeration, air conditioning systems, and heat pumps. In this paper thermal-physical properties of nanoparticles suspended in refrigerant and lubricating oils of refrigerating systems were reviewed. The effects of nanolubricants on boiling and two phase flow phenomena are presented as well. Based on results available in the literatures, it has been found that nanorefrigerants have a much higher and strongly temperature-dependent thermal conductivity at very low particle concentrations than conventional refrigerant. This can be considered as one of the key parameters for enhanced performance for refrigeration and air conditioning systems. Because of its superior thermal performances, latest up to date literatures on this property have been summarized and presented in this paper as well. The results indicate that HFC134a and mineral oil with TiO2 nanoparticles work normally and safely in the refrigerator with better performance. The energy consumption of the HFC134a refrigerant using mineral oil and nanoparticles mixture as lubricant saved 26.1% energy with 0.1% mass fraction TiO2 nanoparticles compared to the HFC134a and POE oil system.